Reporting issues challenging the National Roads Authority of Papua New Guinea: the case for using local indigenous mechanisms - Brown, Alistair (Routledge Taylor & Francis Group, 2015)
For many years, considerable resources have been expended on the National Roads Authority of Papua New Guinea to help build up and maintain the road assets for the economic and social development of Papua New Guinea. Evidence from the audit reports of the auditor-general of Papua New Guinea suggests that there appears room to improve the reporting and accountability of this authority through local indigenous mechanisms. The paper is an important warning for donor organizations about opportunism and how to prevent it (and worse).